Performance analysis of uplink CDMA cellular systems based on the large system method - YU Kai1; FAN Ping-zhi2; HAO Li2 (Tongxin xuebao)
The performance of uplink of CDMA cellular systems with large and small scale fading was investigated based on the large system analysis.The intra-cell multiple access interference was firstly analyzed as well as the inter-cell in-terference.Then the signal to interference and noise ratio was deduced,the result of which was only dependent on the cell load,user power and channel coefficient.Finally,the bit error rate,throughput and spectrum efficiency were analyzed,which were confirmed by simulations.The simulation results show that as the cell load increases,the bit error rate in-creases and the throughput decreases.However,the spectrum efficiency increases monotonously.